First Case of VIM-1-like-Producing Pseudomonas putida Bacteremia in an Oncohematological Pediatric Patient in Italy - Venere Cortazzo; Marilena Agosta; Stefania Gaspari; Gianluca Vrenna; Barbara Lucignano; Manuela Onori; Valentina Di Ruscio; Livia Mancinelli; Danielle Domo; Carlo Federico Perno; Paola Bernaschi (MDPI AG, 2023)
Bacterial infections caused by multidrug-resistant (MDR) Gram-negatives are of great concern worldwide, as they are frequently associated with high mortality and morbidity rates. To date, two cases of VIM-2 metallo-β-lactamase (MBL)-producing Pseudomonas putida bacteremia have been ever reported in France and Spain between 2004 and 2010. Here, we present the first case of VIM-1-like-producing P. putida isolated in blood culture collected from an oncohematological pediatric patient admitted to Bambino Gesù Children's Hospital (IRCCS) in Rome, Italy.